2009
DOI: 10.1161/circinterventions.109.852178.109.852178
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Eluting Stent Thrombosis in Routine Clinical Practice

Abstract: for the ARRIVE 1 and ARRIVE 2 Participating Physicians Background-Stent thrombosis (ST) is an uncommon but serious complication of drug-eluting and bare metal stents.To assess drug-eluting stent ST in contemporary practice, we analyzed 2-year data from the 7492-patient ARRIVE registry. Methods and Results-Patients were enrolled at the initiation of percutaneous coronary intervention with no inclusion/ exclusion criteria beyond use of the paclitaxel-eluting TAXUS stent. Two-year follow-up was 94% with independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Still, a survival bias may have occurred because out-of-hospital deaths as a result of ST were not included in our cohort. Second, as ST is an uncommon complication of PCI, our ST group of 83 patients (4.8% of the entire study population) is consistent with previous reports [8,9,10], and thus could be underpowered to detect differences between the ST subgroups. Third, only serum creatinine level at admission was used to assess basic renal function as previously done [6,7], which might be a source of error as the MDRD equation requires a stable creatinine level which might not be the case in STEMI patients.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Still, a survival bias may have occurred because out-of-hospital deaths as a result of ST were not included in our cohort. Second, as ST is an uncommon complication of PCI, our ST group of 83 patients (4.8% of the entire study population) is consistent with previous reports [8,9,10], and thus could be underpowered to detect differences between the ST subgroups. Third, only serum creatinine level at admission was used to assess basic renal function as previously done [6,7], which might be a source of error as the MDRD equation requires a stable creatinine level which might not be the case in STEMI patients.…”
Section: Discussionsupporting
confidence: 85%
“…In previous reports, CKD was an independent risk factor for ST [9,10,11,12,13]. Breet et al [14] reported a higher rate of on-clopidogrel and on-aspirin platelet reactivity in patients with eGFR <60 mL/min/1.73 m 2 compared with those with higher eGFR.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations